Strategy of Avian Influenza Vaccine Development As a Step to Control - Syamsidar Syamsidar; Jono M Munandar; Eko Ruddy Cahyadi; Aprilia Kusumastuti (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
Avian Influenza Disease (AI) is a disease that can cause high mortality up to 100% in laying hens so it is very harmful. One of the strategic steps of AI disease control and prevention is vaccination by inducing immunity before infection with avian influenza disease. AI vaccine development strategy is needed to increase the company's market share of the organization. The purpose of this research is to analyze the development strategy of AI vaccine according to the requirement of laying chicken breeder in West Java. Data analysis uses quality function deployment (QFD). The result of the research indicates that the consumer's priority of absolute weight is the composition (5,51), laboratory service (3,78), certification (3,42) and price (3,33). Technical requirements as a step to translate customer requirements into technical steps to achieve a match between AI vaccines developed with consumer desires from absolute weight values is to make coctail compositions 89, set competitive prices (75), to vary the packaging volume (64) ) and from the relative weight value of making the coctail composition 88, setting the competing price (65), making the product innovation a viral content update based on disease progression in the field (56), making the smaller dosage pack volume (55). Managerial implications based on research results which is recommended to manufacturers to meet consumer needs is to focus on development, improvement, planning and control to the priority of the variables that are concerned with designing AI vaccine products.Keywords: avian influenza, laying hens, strategies of improving, vaccine AI, quality function deployment